Comparison of AOPs Efficiencies on Phenolic Compounds Degradation - Lourdes Hurtado; Deysi Amado-Piña; Gabriela Roa-Morales; Ever Peralta-Reyes; Eduardo Martin del Campo; Reyna Natividad (Journal of Chemistry)
In this work, a comparison of the performances of different AOPs in the phenol and 4-chlorophenol (4-CP) degradation at lab and pilot scale is presented. It was found that, in the degradation of phenol, the performance of a coupled electro-oxidation/ozonation process is superior to that observed by a photo-Fenton process. Phenol removal rate was determined to be 0.83 mg L−1 min−1 for the coupled process while the removal rate for photo-Fenton process was only 0.52 mg L−1 min−1. Regarding 4-CP degradation, the complete disappearance of the molecule was achieved and the efficiency decreasing order was as follows: coupled electro-oxidation/ozonation > electro-Fenton-like process > photo-Fenton process > heterogeneous photocatalysis. Total organic carbon was completely removed by the coupled electro-oxidation/ozonation process. Also, it was found that oxalic acid is the most recalcitrant by-product and limits the mineralization degree attained by the technologies not applying ozone. In addition, an analysis on the energy consumption per removed gram of TOC was conducted and it was concluded that the less energy consumption is achieved by the coupled electro-oxidation/ozonation process.